2004
DOI: 10.1002/app.20693
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash particles and precipitated silica as fillers in rubbers. I. Untreated fillers in natural rubber and styrene–butadiene rubber compounds

Abstract: ABSTRACT:In this study, we investigated the effects of untreated precipitated silica (PSi) and fly ash silica (FASi) as fillers on the properties of natural rubber (NR) and styrenebutadiene rubber (SBR) compounds. The cure characteristics and the final properties of the NR and SBR compounds were considered separately and comparatively with regard to the effect of the loading of the fillers, which ranged from 0 to 80 phr. In the NR system, the cure time and minimum and maximum torques of the NR compounds progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 58 publications
1
119
0
Order By: Relevance
“…The demand for the light weight materials such as for surfaces of ships had led to the development of fly -ash based thermosetting resins [2][3][4][5][6]. In fibre epoxy composites the addition of fly ash led to a reduction of the density and increase in modulus of composites [4].…”
Section: Introductionmentioning
confidence: 99%
“…The demand for the light weight materials such as for surfaces of ships had led to the development of fly -ash based thermosetting resins [2][3][4][5][6]. In fibre epoxy composites the addition of fly ash led to a reduction of the density and increase in modulus of composites [4].…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of silanized and unsilanized fly ash filled unsaturated polyester composites in both uncured and cured states were reported by Sen et al [10] They observed a lower cure rate in case of silanized fly ash filled composites and a higher cure rate in case of unsilanized flyash-filled composites compared to the neat resin. Sombatsompop et al [11] reported a comparative study on the use of fly ash and precipitated silica as fillers in rubbers. They observed discrepancies in the results between precipitated silica and fly ash silica for different rubber matrix systems and concluded that the filler-filler interactions, actual rubber content in the vulcanizates and particle size of the fillers were responsible for such discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the other substances were added to reduce the silica crystallization and improve the filler dispersion. During this procedure, the siloxane (-Si-O-Si) and silanol (-Si-OH) on the silica surfaces easily react with silane and PEG, reducing the surface polarity (by breaking the cross-linking agents, especially polysulfide), and hence increasing their hydrophobicity [12]. This chemical change improves the compatibility with rubber and reduces the silica absorption that otherwise prolongs vulcanization in the MgCO 3 Fig.2 vulcanizates.…”
Section: Cure Propertiesmentioning
confidence: 99%